MP44: Emergency department perceptions of routine in-situ simulation. (May 2019) - Cox, C.; Stewart, S.; Patrick, L.; Sowers, N.
Abstract : Introduction : Emergency Department (ED) health care professionals are responsible for providing team-based care to critically ill patients. Given this complex responsibility, simulation training is paramount. In situ simulation (ISS) has many cited benefits as a training strategy that targets on-duty staff and occurs in the actual patient environment. Several evidence-based frameworks identify staff buy-in as essential for successful ISS implementation, however, the attitudes of interdisciplinary front-line ED staff in this regard are unknown. The purpose of this study is to identify contextual trends in interdisciplinary opinions on routine ISS in the ED.Methods : Qualitative and quantitative review, exploring the self-reported attitudes of interdisciplinary ED staff: before, during and after the implementation of a routine ISS pilot program (5 sessions in 5 months) at the Charles V Keating Emergency and Trauma Center in Halifax from Feb-Nov, 2018.Results : 149 surveys were received. Baseline support for ISS was high; 83% of respondents believed that the advantages of ISS outweigh the challenges and 47% favoured simulation in the ED, relative the sim bay (26%) and 28% were indifferent. The attitudes of direct participants in ISS were very positive, with 88% believing that the benefits outweighed the challenges after participation and 91% believing that they personally benefited from participating. A department wide post-ISS pilot survey suggested a slight decrease in support. Support for ISS dropped from 83% to 67%, a statistically insignificant reduction (p = 0.098) but a sizeable change that warrants further investigation. Most notably respondents reported increased support for simulation training in a simulation bay relative to ISS in the ED. Respondents still regarded simulation highly overall. Interestingly, when the results were stratified by position, staff physicians were the least positive.Conclusion : Pre-pilot or baseline opinions of ISS were very positive, and participants all responded positively to the simulations. This study generates valuable insight into the perceptions of interdisciplinary ED staff regarding the implementation and perceived impact of routine ISS. This evidence can be used to inform future programming, though further investigation is warranted into why opinions post-intervention may have changed at the department level.